Regional Clinical and Biochemical Differences among Patients with Primary Hyperparathyroidism - GÜLLÜOĞLU, MAHMUT BAHADIR; UĞURLU, MUSTAFA ÜMİT (GALENOS YAYINCILIK, 2017)
Background: Environmental habitat may play a role in clinical disparities of primary hyperparathyroidism (pHPT) patients. Aims: To compare preoperative clinical symptoms and associated conditions and surgical findings in patients with pHPT, living in different geographical regions from the Black Sea, Mediterranean and Anatolia regions. Study Design: Retrospective, clinical-based multicentric study of 694 patients with pHPT. Methods: Patients from 23 centers and 8 different geographical regions were included. Data related to baseline demographics, clinical, pathologic and treatment characteristics of 8 regions were collected and included age, gender, residential data, symptoms, history of fracture, existence of brown tumor, serum total Ca and p levels, serum parathormone (PTH) levels, serum 25-OH vitamin D levels, bone mineral density, size of the resected abnormal parathyroid gland(s), histology, as well as the presence of ectopia, presence of dual adenoma, and multiple endocrine neoplasia (MEN)- or familial-related disease. Results: The median age was 54. Asymptomatic patient rate was 25%. The median PTH level was 232 pg/mL and serum total Ca was 11.4 mg/dL. Eighty-seven percent of patients had an adenoma and 90% of these had a single adenoma. Hyperplasia was detected in 79 patients and cancer in 9 patients. The median adenoma size was 16 mm. Significant parameters differing between regions were preoperative symptoms, serum Ca and p levels, and adenoma size. All patients from South-East Anatolia were symptomatic, while the lowest p values were reported from East Anatolia and the largest adenoma size, as well as highest Ca levels, were from Bulgaria. Conclusion: Habitat conditions vary between geographical regions. This affects the clinicopathological features of patients with pHPT.
Keywords: Hyperparathyroidism; clinocopathological features; regional differences; Turkey; Bulgaria; VITAMIN-D STATUS; PARATHYROID ADENOMA WEIGHT; D DEFICIENCY; EPIDEMIOLOGY; POPULATION; CARCINOMA; IMPACT